1999
DOI: 10.1177/002205749918100305
|View full text |Cite
|
Sign up to set email alerts
|

Geography Teaching and the New Technologies: Opportunities and Challenges

Abstract: Technology has revolutionized geography as a profession and has had a significant impact on the teaching of the subject in K–12 and higher education. Geographic Information Systems (CIS) have transformed the work of professional geographers and university geography faculty. GIS is also a powerful technology for geography teachers at the pre-college level. With this new tool, students can engage in serious inquiry about issues of local and global significance using authentic data. Current research findings abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…GIS has been used within higher education (HE) contexts almost since its inception; however, its use in secondary schools did not start until the early 1990s (Kerski et al, 2013) when it began, particularly in the US, to be considered a tool which had the potential to develop students' engagement with technology (Goodchild & Kemp, 1990;Lemberg & Stoltman, 2001). Kerski et al (2013) argue that the rapid increase in GIS use in some global secondary school contexts since then is due mainly to the perceived benefits it provides.…”
Section: A Rationale For Gis In Geographymentioning
confidence: 99%
“…GIS has been used within higher education (HE) contexts almost since its inception; however, its use in secondary schools did not start until the early 1990s (Kerski et al, 2013) when it began, particularly in the US, to be considered a tool which had the potential to develop students' engagement with technology (Goodchild & Kemp, 1990;Lemberg & Stoltman, 2001). Kerski et al (2013) argue that the rapid increase in GIS use in some global secondary school contexts since then is due mainly to the perceived benefits it provides.…”
Section: A Rationale For Gis In Geographymentioning
confidence: 99%
“…At the beginning of 1990s, GIS was increasingly seen as an essential element which could introduce secondary school students to the use of technology, and spur them to be motivated in careers in science and engineering [5] . The interest in this area has increased at the secondary school level after many other studies revealed that GIS is an educational tool rather than a technology and contributes to creating an inquiry based learning environment [6,7,8,9,10,11] . Due to these pedagogical advantages, GIS has found a place in secondary school curriculums in diverse programs including Science, Chemistry, Biology, Mathematics, Environmental and Social Sciences along with Geography in the USA, Canada, and Europe [10,12,13,14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of "Teaching about GIS" is mainly to teach GIS technologies. The overall opinion among the educators about the type of the use of GIS in geographic education focuses on "Teaching with GIS" [9,12,14] . Nonetheless, Johansson [19] has mentioned that it is necessary to revert to the 'Teaching about GIS' to some extent before using GIS in classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies done on GIS in education in the international context indicated that in addition to increasing student and teacher motivation, GIS are very effective tools for incorporating project-based teaching and learning, and promoting students' geographic skills such as thinking geographically, analyzing and synthesizing spatial data, map reading and interpreting (Tinker, 1992;Geography Education Standards Project [GESP], 1994;Palladino, 1994;Audet & Abegg, 1996;Lemberg & Stoltman, 1999;Pottle, 2001;Shin, 2006). Tinker (1992), Palladino (1994), and Audit & Abegg (1996), who were the leading academicians, conducted the first research on education with GIS and underlined the positive relationships between education with GIS and the development of spatial skills of the students.…”
Section: Introductionmentioning
confidence: 99%